Presencia del enfoque intercultural en representaciones docentes sobre lo juvenil, la diversidad y la cultura rural - Morales-Trejos, Carol (Universidad de Costa Rica, 2018)
This scientific article presents results of the research project "Teaching Pedagogical Practices in Contexts of Rural Youth Interaction, of the Great Metropolitan Area of Costa Rica: a look from Intercultural Education" registered in the Institute of Investigations in Education (INIE) of the University of Costa Rica, in the 2016-2017 period. This paper gives an account of experiences in rural education at the secondary level of the teaching representations about youth, diversity and rural culture and how these are articulated in the professional work. At the methodological level, the research is based on the hermeneutic-interpretative approach, from which in-depth interviews were conducted with 11 teachers from three Rural Technical High Schools of the Greater Metropolitan Area of Costa Rica. This paper considers results corresponding to the second and third specific objectives of this research associated with "identifying teaching representations about youth, diversity and rural culture, as well as the notions and principles of the intercultural approach present in the pedagogical practices studied", pointing out within the main findings the breadth of teaching criteria regarding the concepts studied. Likewise, intercultural approaches are recognized in the teaching action from the specificity of the historical and social contexts in which said practices are carried out. Specifically, it shows the representation that the professional person in education, which forms a form of knowledge through which the person who knows is placed within what he knows and acts accordingly.